PENGARUH SHOPPING LIFESTYLE DAN FASHION INVOLVEMENT TERHADAP IMPULSE BUYING BEHAVIOR (Studi Kasus Pembelian Hijab Pada Mahasiswi Fakultas Ekonomi Universitas Islam Malang) - Anggi Mita Wijaya; Muhammad Hufron; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACT The study in aim to know influence shopping lifestyle and of fashion involvement by simultan to Impulse buying behavior and influence of shopping lifestyle and fashion involvement by parsial to impulse buying behavior. The type study is explanatory research. This research done in University of Islamic Malang. Population in this research is all student Faculty Of Economics University Islamic Malang 2013-2016 amounting to 1461 while research sampel amount to 100 respondent with sampling technique of accidental sampling.  Result of research indicate that by parsial shopping lifestyle have an effect on to impulse buying behavior and fashion involvement have an effect on signifikan by parsial to impulse buying behavior. By simultan shopping lifestyle and fashion involvement have an effect to environmental impulse buying behavior Student of Faculty Economics University of Islamic Malang. Keywords        :           Shopping Lifestyle, Fashion Involvement Impulse Buying Behavior